Advancements and Emerging Strategies in Mechanical Ventilation: A Systematic Review of Innovative Modalities, Monitoring Technologies, and Prevention of Ventilator-Induced Injuries - Ravi Yadav (CV Media Inti Teknologi, 2026)
Background: Mechanical ventilation remains essential for patients with respiratory failure and during anesthesia for surgery. Despite technological progress, challenges persist regarding optimal ventilatory settings, transition strategies between non-invasive and invasive ventilation, and prevention of ventilator-induced lung injury and ventilator-induced diaphragm dysfunction.Aims: To comprehensively review recent advances in mechanical ventilation, focusing on innovative ventilation modes, monitoring technologies, and strategies to prevent ventilator-induced complications.Methods: A systematic review was conducted following PRISMA guidelines. Literature searches were performed in PubMed, EMBASE, and the Cochrane Library for studies published between January 2020 and October 2025. Clinical efficacy, safety, and patient outcomes across ventilation modalities were assessed. Thirty-five randomized controlled trials and high-quality observational studies were included for primary analysis, with fifteen additional studies supporting discussion findings.Results: Significant progress was identified in several areas of mechanical ventilation. Neurally Adjusted Ventilatory Assist (NAVA) improved patient-ventilator synchrony and increased ventilator-free days compared with conventional modes (22 vs. 18 days, p = 0.016). Adaptive Support Ventilation demonstrated comparable efficacy to standard ventilation while reducing clinician workload. Proportional Assist Ventilation showed no significant advantage over pressure support ventilation in liberation time (7.3 vs. 6.8 days, p = 0.58). Artificial intelligence-based monitoring systems achieved >95% sensitivity in detecting patient-ventilator asynchronies. Lung-protective ventilation with low tidal volumes and plateau pressures <30 cmH₂O remained the cornerstone of ARDS management.Conclusion: Novel ventilation modes may enhance synchrony and reduce workload, although major clinical benefits remain limited. Artificial intelligence shows promise for personalized ventilation strategies, while lung-protective ventilation remains critical for preventing VILI.